Lysine demethylases and cancer - Eckschlager, Tomas; Vicha, Ales; Frolikova, Daniela (Pathology, research and practice, 2025)
Epigenetic mechanisms are of pivotal importance in the normal development and maintenance of cell and tissue-specific gene expression patterns, and are fundamental to the genesis of cancer. One significant category of epigenetic modifications is histone methylation. Histone methylation plays a crucial role in the regulation of gene expression, and its dysregulation has been observed in various diseases, including cancer. The maintenance of the histone methylation state is dependent on two classes of enzymes: histone methyltransferases, which add methyl groups to arginine and lysine residues, and lysine demethylases, which remove methyl groups from lysine residues of histones. To date, eight subfamilies have been identified, comprising approximately 30 lysine demethylases. These enzymes are expressed differently across cells and tissues and exert a substantial impact on the development and progression of cancer. The diverse range of lysine demethylases influence a multitude of oncogenic pathways, either by promoting or inhibiting their activity. However, comprehensive data on the full spectrum expression of lysine demethylases in distinct cancer types remain scarce. Lysine demethylases have been demonstrated to play a role in drug resistance in numerous cancers. This is achieved by modulating the metabolic profile of cancer cells, enhancing the ratio of cancer stem cells, and elevating the expression of drug-tolerant genes. Additionally, they facilitate epithelial-mesenchymal transition and metastatic potential. The objective of this review is to synthesize recent data on the relationship between lysine demethylases and cancer, with a particular focus on cancer cell drug resistance.
Keywords: Neoplasms; regulace genové exprese u nádorů; Gene Expression Regulation, Neoplastic; nádory; Animals; Histone Demethylases; epigeneze genetická; lidé; epitelo-mezenchymální tranzice; zvířata; histondemethylasy; Epigenesis, Genetic; Epithelial-Mesenchymal Transition; Humans